2014
DOI: 10.4028/www.scientific.net/amr.955-959.3655
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrogen Deposition on Soil Nutrient Content of <i>Deyeuxia angustifolia</i>

Abstract: Taking the marsh meadowDeyeuxia angustifoliain San Jiang Plain of Northeast China as test material,a field experiment was carried out with treatments different in nitrogen supply (0,4,8g/m2) to investigate the effects the soil nutrient content.The results showed that difference among layers soil organic matter activity firstly increased and then decreased with increasing of nitrogen addition. Difference among layers soil total nitrogen contains were no significant differences. Soil total nitrogen contains redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…According to the environmental factors predicted by the model, the most important factor affecting D. angustifolia is total nitrogen, which is one of the factors affecting the species composition, diversity, and nutritional conditions, as the enrichment of nitrogen changes the content of soil nutrients (Fu et al, 2014). Numerous studies have found that the increase in nitrogen promotes the growth of D. angustifolia, increases its productivity, and enhances its competitiveness (Jin et al, 2016), making it a dominant species in the environment, which is consistent with the results obtained in this study.…”
Section: Influencing Factors Affecting the Change Of Suitable Habitat...mentioning
confidence: 99%
“…According to the environmental factors predicted by the model, the most important factor affecting D. angustifolia is total nitrogen, which is one of the factors affecting the species composition, diversity, and nutritional conditions, as the enrichment of nitrogen changes the content of soil nutrients (Fu et al, 2014). Numerous studies have found that the increase in nitrogen promotes the growth of D. angustifolia, increases its productivity, and enhances its competitiveness (Jin et al, 2016), making it a dominant species in the environment, which is consistent with the results obtained in this study.…”
Section: Influencing Factors Affecting the Change Of Suitable Habitat...mentioning
confidence: 99%